Prevalence and Characteristics of Neuropathic Pain in Patients With Spinal Cord Injury Referred to a Rehabilitation Center - Hae Young Kim; Hye Jin Lee; Tae-lim Kim; EunYoung Kim; Daehoon Ham; Jaejoon Lee; Tayeun Kim; Ji Won Shin; Minkyoung Son; Jun Hun Sung; Zee-A Han (Annals of Rehabilitation Medicine, 2020)
Objective To identify the prevalence and characteristics of neuropathic pain (NP) in patients with spinal cord injury (SCI) and to investigate associations between NP and demographic or disease-related variables. Methods We retrospectively reviewed medical records of patients with SCI whose pain was classified according to the International Spinal Cord Injury Pain classifications at a single hospital. Multiple statistical analyses were employed. Patients aged <19 years, and patients with other neurological disorders and congenital conditions were excluded. Results Of 366 patients, 253 patients (69.1%) with SCI had NP. Patients who were married or had traumatic injury or depressive mood had a higher prevalence rate. When other variables were controlled, marital status and depressive mood were found to be predictors of NP. There was no association between the prevalence of NP and other demographic or clinical variables. The mean Numeric Rating Scale (NRS) of NP was 4.52, and patients mainly described pain as tingling, squeezing, and painful cold. Females and those with below-level NP reported more intense pain. An NRS cut-off value of 4.5 was determined as the most appropriate value to discriminate between patients taking pain medication and those who did not. Conclusion In total, 69.1% of patients with SCI complained of NP, indicating that NP was a major complication. Treatment planning for patients with SCI and NP should consider that marital status, mood, sex, and pain subtype may affect NP, which should be actively managed in patients with an NRS ≥4.5.